CXCR4 expression accounts for clinical phenotype and outcome in acute myeloid leukemia. Issue 5 (5th February 2014) - Mannelli, Francesco; Cutini, Ilaria; Gianfaldoni, Giacomo; Bencini, Sara; Scappini, Barbara; Pancani, Fabiana; Ponziani, Vanessa; Bonetti, Maria Ida; Biagiotti, Caterina; Longo, Giovanni; Bosi, Alberto
<x xml:space="preserve">Abstract</x> Background In acute myeloid leukemia (AML), CXCR4 expression has been correlated with leukocytosis and prognosis. Methods We quantified CXCR4 expression by flow cytometry on leukemic cells in 142 AML patients. Results We confirm a correlation between high CXCR4 expression and leukemic burden. Furthermore, we documented a correlation with platelet count, dysplastic megakaryopoiesis, hepato‐splenomegaly and extra‐hematological disease. NPM1‐mutated AML displayed a significantly higher intensity of CXCR4 compared to NPM1‐wt cases: it is conceivable its clinical phenotype to be driven by high CXCR4 expression. Conclusions CXCR4 expression resulted in an independent prognostic factor. Our data support CXCR4 targeting as a potential therapeutic strategy. © 2014 International Clinical Cytometry Society